ANTI-RO ANTIBODY POSITIVITY AND ITS RELATIONSHIP WITH PULMONARY INVOLVEMENT IN SYSTEMIC SCLEROSIS - Aydın, Umut; Akar, Zeynel Abidin; Karataş, Ahmet; Öz, Burak (My University, 2025)
Aim: Pulmonary involvement is a major contributor to both morbidity and mortality in systemic scle-rosis (SSc). While specific autoantibodies, such as anti-Scl-70 and anti-centromere, have been linked to distinct disease subtypes and organ complications, the role of anti-Ro antibodies in SSc—particularly in relation to pulmonary manifestations—has not been fully elucidated. Understanding this relationship may provide insights into disease stratification and risk assessment for lung involve-ment in SSc patients. This study aimed to determine the prevalence of anti-Ro antibodies in patients with SSc and to investigate their potential association with pulmonary complications, including inter-stitial lung disease and pulmonary arterial hypertension. Material and Methods: We retrospectively reviewed 73 patients with SSc who underwent anti-Ro anti-body testing, chest X-rays, and high-resolution computed tomography (HRCT). Serum levels of anti-Scl-70, anti-centromere, anti-Ro, and anti-La antibodies were measured using enzyme-linked im-munosorbent assay, with a positivity threshold of ?21 IU/mL, while antinuclear antibodies (ANA) were assessed via indirect immunofluorescence. Pulmonary changes were evaluated by imaging, with par-ticular attention to reticular patterns, ground-glass opacities, and honeycombing. Results: ANA positivity was observed in 94.5% of patients. Anti-Scl-70 and anti-centromere antibodies were detected in 52.8% and 18.8% of patients, respectively. Anti-Ro antibodies were positive in six patients (8.2% of the cohort); all were also ANA-positive. Two patients (2.7% of the cohort) were posi-tive for anti-Scl-70, while none exhibited anti-centromere antibodies. Pulmonary abnormalities were more frequently observed in anti-Ro-positive patients on both chest radiographs and HRCT, although these differences did not reach statistical significance. Conclusion: Anti-Ro antibodies were uncommon in SSc, but were associated with a non-significant trend toward increased pulmonary involvement. Larger prospective studies, especially evaluating anti-Ro52, are needed to clarify their clinical relevance.
Keywords: Autoantibodies; Systemic sclerosis; pulmonary involvement; interstitial lung disease; anti-Ro antibodies